THE REGIME OF STRAITS: SAFETY, SECURITY AND PROTECTION OF THE MARINE ENVIRONMENT - Oral, Nilufer (Martinus Nijhoff, 2013)
[Abstract Not Available]
Law-of-the-Sea-Institute Conference on Institutions and Regions in Ocean Governance -- OCT, 2010 -- Int Tribunal Law Sea, Hamburg, GERMANY
Keywords: Compulsory Pilotage; Convention; Navigation; Passage; Law